Detection of Microbial Contamination and Hormonal Residues of Crispy Chicken available in Local Markets - Aliaa Saadoon Abdulrazaq Al-Faraji (Journal of Global Pharma Technology, 2018)
The study aimed to knowing the contamination range in some cover Crispy Chicken samples imported for Iraq by evolution the microbial contamination and levels of some hormones , packaged food samples included 14 different types of crispy chicken are : C1 ,C2,C3,C4,C5,C6,C7,C8,C9,C10,C11,C12,C13,C14, The results shown for microbial assays of the sample C6 that contain 6.3 ×10 8 wt m /gm meat total number of aerobic bacteria by using BacTRAC 4300 Device , either sample C11 was a violation of health conditions with contained of Salmonella bacteria . According to the levels some hormone the result were shown that progesterone hormone have high level of sample C11 which was 15 ng /ml , so the testosterone hormone has been high in samples C1,C7,C8,C9 with rate ˃ 16, ˃ 16, 15.5 , ˃ 16 ng /ml Respectively . It was shown from the results that must all kinds of imported crispy chicken be subjected to constant detection of microbial contamination and hormones because have direct effect of maintaining on general health and customers health especially.Key words:  Crispy chicken, Microbial contamination, Hormones, Bactrac device.